Development of Tourism as a Social Phenomenon in the Conditions of Globalization - KOKHAN, Tatiana Anatolyevna; ZHIRNOVA, Elena Vladimirovna; LAZUTINA, Nataliia Stanislavovna; VINIUKOVA, Elena Aleksandrovna; MISHUROVA, Olga Ivanovna (Journal of Environmental Management and Tourism, 2019)
The article is devoted to the elaboration of approaches to the development of tourism as a social phenomenon in the conditions of globalization. It has been established that tourism is more stable compared with other industries in the conditions of uncertainty in global markets. Social advantages of tourism are the satisfaction of leisure needs, higher living standards of the population following an inflow of foreign currencies, the development of small entrepreneurship, the implementation of national social policies, new jobs, multiplicative effect from tourism, regional development in the conditions of globalization and cross-cultural communication. The authors have highlighted proposals aimed to develop tourism in the conditions of globalization and cross-cultural communication, which include efforts to improve tourism legislation and legislative initiatives aimed to make conceptual amendments to legislative acts in order to prioritize real providers of tourist services.